STRATEGI KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN SD NEGERI 03 SUNGAYANG - Yulmawati, Yulmawati (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2016)
This research aimed at describing the strategy of principal on upgrading the educational quality of Primary School 03 Sungayang. Type of this research was qualitative, case study. Data were collected by using observation, interview and documentation. The results were 1) the planning by organizing the strategic school program; 2) the program implementation by upgrading school discipline, upgrading score of National Examination, holding extracurricular and cooperating with the society.Â Keywords: Principalâs Strategy, Educational Quality, Primary School 03 Sungayang